Safe menstrual hygiene management practice and associated factors among female adolescent students at high schools in central Ethiopia: A mixed–method study - Deriba, Berhanu Senbeta; Garedew, Girma; Gemeda, Diriba; Geleta, Tinsae Abeya; Jemal, Kemal; Bala, Elias Teferi; Mekuria, Mulugeta; Nigussie, Tadesse; Dirirsa, Dejene Edosa; Legesse, Elsabeth (Frontiers in Public Health, 2022)
Background: Menstrual Hygiene Management (MHM) is a much-neglected issue in developing countries, including Ethiopia. Menstruating women and girls are forced into isolation, prevented from movement, dietary restrictions, and can be prevented from participating in daily routine activities. Furthermore, the way almost all previous studies conducted in Ethiopia measured the practice of MHM did not meet standard definition of safe MHM. This study aimed to assess safe management of menstrual hygiene practice and associated factors among female adolescent students in public high schools in central Ethiopia. Methods: A mixed-methods approach was employed in this study. Systematic random sampling technique was used to select 846 study participants. The collected data were entered through EPI INFO version 7 and exported to SPSS version 23 for cleaning and analysis. Bivariate and multivariate logistic regression analysis were performed to identify the association between MHM and independent variables. Finally, AOR, 95% CI, and p-value < 0.05 were considered statistically significant. The qualitative data was analyzed by ATLAS.ti in order to extract the main themes and categories. Direct quotations were presented with a thick description of the findings. Results: The safe management of menstrual hygiene was 28.20%. Living with parents (AOR=2.51, 95% CI:1.11-5.68), living with relatives (AOR=7.41, 95% CI:2.55-21.54), having a merchant mother (AOR=1.81, 95% CI:1.14-2.9), having a mother who has private work (AOR=4.56, 95% CI:1.31-5.90), having a farmer father (AOR=1.53, 95% CI:1.1-2.31), rural resident (AOR=1.61, 95% CI: 1.17-2.21) and realizing the absence of container for storing sanitary napkins in the toilet of the school latrine (AOR=1.44, 95% CI: 1.1-0.94) were factors associated with MHM. Findings from a qualitative study were discussed under four themes to explore barriers to menstrual hygiene management, and three themes emerged as enablers to menstrual hygiene management. Conclusions: The safe management of menstrual hygiene was low among adolescent girls. People with whom adolescent girls live, the occupational status of mother and father, residence, the availability of a container to dispose of sanitary napkins in school toilets were factors associated with menstrual hygiene management. Behavioral change communications must be provided to female students about menstrual hygiene.